Orthostatic hypotension: From pathophysiology to clinical applications and therapeutic considerations. Issue 5 (22nd March 2019) - Magkas, Nikolaos; Tsioufis, Costas; Thomopoulos, Costas; Dilaveris, Polychronis; Georgiopoulos, Georgios; Sanidas, Elias; Papademetriou, Vasilios; Tousoulis, Dimitrios
Abstract : Orthostatic hypotension (OH), that is blood pressure fall when standing from the supine to the erect position, is a common cardiovascular disorder, highly prevalent in elderly and frail individuals and in patients with multiple comorbidities. Orthostatic hypotension is considered a manifestation of dysfunction of the autonomic nervous system, caused or facilitated by several neurological or non‐neurological diseases and conditions, while its clinical significance is increasingly recognized as a cause of impairment of quality of life and potentially of worse outcomes. Indeed, OH has been extensively studied and numerous prospective cohort studies support its association with adverse events, including coronary artery disease, heart failure, stroke, cognitive dysfunction, and, most importantly, mortality rates. Specific pharmacological and non‐pharmacological interventions have been established for the treatment of OH. However, randomized data evaluating the impact of therapeutic interventions on morbidity and mortality outcomes are lacking. Thus, despite that OH seems to have important prognostic implications indicated by several reported associations with adverse events, it remains unclear whether OH treatment could improve prognosis. In the present review, we discuss the clinical applications associated with ΟΗ by outlining the current perspectives on ΟΗ definition, diagnosis, pathophysiology, prognostic role, and treatment.